PERCEPTIONS OF MULTINATIONAL STUDENTS ON SUNDANESE GASTRONOMY READING ENRICHMENT ASSISTED BY AUGMENTED REALITY FOR BIPA LEARNERS - Jessie Mulyanie; Nuny Sulistiany Idris; Mochamad Whilky Rizkyanfi (RADJA PUBLIKA, 2025)
This study aims to provide reading learning materials enriched with Augmented Reality (AR) using Sundanese Gastronomy for non-native Indonesian language learners (BIPA). This study emphasizes the importance of incorporating local culture into language education and the limited use of interactive technologies, such as Augmented Reality, in BIPA classes. This study used a descriptive qualitative methodology, including an open-ended questionnaire for data collection from six BIPA learners representing various countries. The collected data were analyzed thematically to reveal learners’ responses, needs, and perspectives on the resulting learning materials. The results showed that all participants had no prior experience with AR media but showed significant interest in its use in learning. The resulting learning tools improved reading comprehension, interestingly presented Indonesian culture, and stimulated more active learning. The application of Sundanese Gastronomy in reading materials provided an authentic cultural background, while the Augmented Reality (AR) aspect enhanced visualization and participation in learning. The findings suggest that creating AR-based reading materials that integrate local culture can provide a new approach to enhance interactive, contextual, and intercultural BIPA learning.